A review on conventional passive cooling methods applicable to arid and warm climates considering economic cost and efficiency analysis in resource-based cities. (November 2021) - Song, Yan-ling; Darani, Kamyar Sheykhi; Khdair, Adnan I.; Abu-Rumman, Ghaida; Kalbasi, Rasool
Abstract: Application of the passive approach as a non-mechanical method is an effective technique to tackle high energy consumption as well as diminishing the destructive effects of buildings on the environment. Using passive cooling can lead to peak load reduction as well as peak load offset, diminishing the interior temperature fluctuation, maintaining indoor air temperature in a comfortable range which consequently reduces fossil fuel usage as well as decrease the greenhouse gas emission. In this study, using passive approach from the economic point of view was discussed. The competition between cost saving (owing to applying passive methods) and added cost (owing to the initial investment, maintenance and operation cost) can specify the usefulness and effectiveness of using passive techniques. In this regard, special points such as building function, ventilation requirements, sensible and latent heat gains, the ability of any technique to save energy, geographical location, user financial ability, initial investment, maintenance and operation cost, regional climate data should be taken into account. Literature review affirmed that owing to applying passive approaches in building, energy consumption is diminished by 8%–70% (using external shading), 37% (utilizing cool colored paints roof), 25% (Creating green space), 7.88% (construction of the prismatic building), 32%–100% (using vegetation-based wall), 50% (using PCM-base wall), 33% (incorporation of insulation into the wall), 10%–20% (building equipped with solar chimney), 25% (using radiative cooling system). From the economic viewpoint, it was found that through finding optimal passive approaches, life-cycle cost saving reached 52%.